On the practical limitations for the generation of Gunn oscillations in highly doped GaN diodes - Garcia-Sanchez, S. (2023)
Planar Gunn diodes based on doped GaN active layers with different geometries have been fabricated and characterized. Gunn oscillations have not been observed due to the catastrophic breakdown of the diodes for applied voltages around 20-25 V, much below the bias theoretically needed for the onset of Gunn oscillations. The breakdown of the diodes has been analyzed by pulsed I - V measurements at low temperatures, and it has been observed to be almost independent of the geometry of the channels, thus allowing to discard self-heating effects as the origin of the device burning. The other possible mechanism for the device failure is an impact-ionization avalanche due to the high electric fields present at the anode corner of the isolating trenches. However, Monte Carlo simulations using the typical value of the intervalley energy separation of GaN, ϵ1-2 = 2.2 eV, show that impact ionization mechanisms are not significant for the voltages for which the experimental failure is observed. But recent experiments showed that ϵ1-2 is lower, around 0.9 eV. This lower intervalley separation leads to a much lower threshold voltage for the Gunn oscillations, not far from the experimental breakdown. Therefore, we attribute the device's failure to an avalanche process just when Gunn domains start to form, since they increase the population of electrons at the high electric field region, thus strongly enhancing impact ionization mechanisms that lead to the diode failure.